Sequelae Tuberkulosis dengan Hemoptisis Rekurens: [Recurrent Hemoptysis in Sequelae Tuberculosis] - Desilia Atikawati; Isnin Anang Marhana (Jurnal Respirasi, 2015)
Background: Various sequelae and complications can occur in treated or untreated tuberculosis (TB). One of complications in  the lungs is hemoptysis, due to alterations of pulmonary vascular structure. Hemoptysis as TB sequelae can happen recurrently and  massively. Case: We present the case of 31 year old man with recurrent hemoptysis since 1 year before admitted to hospital. Patient had  a history of receiving antituberculosis drugs (ATD) before. Chest xray showed pleural thickening and opacity in right hemithorax with  signs of loss of volume. Bronchoscopy showed active bleeding in lateral segment of right lung middle lobe. Chest CT showed destroyed  right lung. Hemoptysis still existed despite the given conventional therapy, thus patient underwent pulmonary arteriography. The result  showed extensive vascular abnormality in the right lung with arteriovenous fistula on right bronchial artery and aneurysmatic branch of  superior bronchial and inner intercostal arteries. During the procedure, there was no active bleeding, so bronchial artery embolization  was adjourned. Patient then experienced recurrent and massive hemoptysis, thus right pneumonectomy was done. During the surgery,  there was uncontrolled active bleeding that caused the patient’s death. Conclusion: This case illustrates recurrent hemoptysis as one of  severe TB sequelae. In extensive pulmonary vascular abnormality, pneumonectomy can cause uncontrolled active bleeding. Bronchial  artery embolization can be used as an alternative to treat patients with recurrent homptysis.